Market Development Approach: A New Paradigm in Promoting Business Development Services - Neupane, Rabindra Kumar (Quest Journal of Management and Social Sciences, 2021)
Background: Business Development Service (BDS) market is considered as a paradigm shift to traditional approaches in promoting and delivering enterprise support services. BDS is an internationally recognized tool to achieve economic prosperity through the development of Micro, Small, and Medium Enterprises (MSMEs). Most developed and developing nations are promoting BDS for MSME development and employment generation. Micro-Enterprise Development Program (MEDEP) has initiated the BDS market development approach named as Micro-Enterprise Development (MED) model in Nepal since1998. Objective: This article is objectively written to analyze and present the MED model, implementation approach, and MEDEP’s strategies for effective BDS delivery; market development; and sustainability. Method: Secondary as well as primary sources of information have been used to collect data. Secondary data have been triangulated through experts’ opinions. A descriptive methodology has been used while analyzing data. Result: Apart from ME promotion, this article has also briefly presented how MEDEP has contributed to making an enabling environment for sustainable BDS market development in Nepal. MED model was implemented by MEDEP in 10 districts in its first phase (1998-2003). The model is found successfully implemented in all districts of Nepal till the end of MEDEP’s 4th phase in 2018. It is in the process of being replicated in all 753 Local Governments (LGs). Conclusion: MEDEP remarkably found highly contributed to the introduction, development, and growth of the BDS market development approach in Nepal by creating more than 132,000 micro-enterprises, developing institutional frameworks and partnerships modality for service delivery, and creating an enabling policy environment. This approach is found well recognized and replicated in some manner by other government, Non-Government and private BDS providing institutions as well.